Departamento Rosario Vera Peñaloza: un camino de organización y articulación popular - Llorente, Gonzalo; Moyano, María Ester; Mena, Ramiro; Mendez, Carla Rebeca (Estación Experimental Agropecuaria La Rioja, INTA, 2023)
EEA La Rioja